High-temperature-resistant flame-retardant thermoplastic elastomer and preparation method thereof
By using specific components and processing processes in thermoplastic elastomers, the problem of insufficient mechanical properties of existing thermoplastic elastomers at high temperatures is solved, and the high temperature resistance and flame retardant properties are improved, while enhancing its mechanical properties.
Patent Information
- Application Number
- CN202411609913.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
The existing thermoplastic elastomers lack mechanical properties at high temperatures, and it is difficult to take into account both high temperature resistance and flame retardant properties.
Using hydrogenated styrene butadiene block copolymer, paraffin oil, polyethylene wax and carbon nanotube modified benzooxazine and other components, it is processed in a twin-screw extruder and a flat vulcanizer to prepare resistant High temperature flame retardant thermoplastic elastomer.
The high temperature resistance and flame retardant properties of the thermoplastic elastomer are improved, while the mechanical properties are enhanced, achieving a good stretching effect at high temperatures.
Smart Images

Figure BDA0005130674230000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a high temperature resistant and flame retardant thermoplastic elastomer and a preparation method thereof. Background Art
[0002] Thermoplastic elastomer (TPE / TPR), also known as artificial rubber or synthetic rubber, is a material that shows rubber elasticity at room temperature, but can be processed like thermoplastic plastics at high temperatures. Its products have the excellent properties of high elasticity, aging resistance, and oil resistance of traditional cross-linked vulcanized rubber, and at the same time have the characteristics of convenient processing and wide processing methods of ordinary plastics, but its high temperature resistance has not been improved. For example, patent CN106674843A discloses a high temperature resistant thermoplastic elastomer and its preparation method. The high temperature resistant thermoplastic elastomer of the invention has excellent aging resistance and high temperature resistance, but its mechanical properties have not been improved. Summary of the invention
[0003] 1. Technical issues to be solved
[0004] In view of the deficiencies of the prior art, the present invention provides a high temperature resistant and flame retardant thermoplastic elastomer and a preparation method thereof, which has good high temperature resistance, flame retardancy and stretching effects.
[0005] (II) Technical solution
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a high temperature resistant flame retardant thermoplastic elastomer, comprising the following weight components: 40-60 weight parts of hydrogenated styrene butadiene block copolymer, 2-4 weight parts of paraffin oil, 1-3 weight parts of polyethylene wax, and 5-8 weight parts of carbon nanotube modified benzoxazine.
[0007] Preferably, the preparation method of the carbon nanotube-modified benzoxazine is:
[0008] (1) Add 5-aminoisophthalic acid and thionyl chloride to xylene solvent, stir evenly, heat to 75-90° C., react for 3-6 hours, and then remove the solvent by evaporation under reduced pressure to obtain intermediate 1;
[0009] (2) adding sulfaguanidine to anhydrous ethanol solvent, stirring evenly, then adding intermediate 1 and triethylamine catalyst, reacting at 80-100° C. for 6-12 hours, and after completion, cooling to room temperature, filtering, washing, and obtaining intermediate 2;
[0010] (3) adding intermediate 2, an aqueous solution of formaldehyde, and magnolol to a toluene solvent, fully dissolving them, and carrying out a cyclization reaction at 65-90° C. for 10-16 hours. After completion, the reaction is carried out by vacuum distillation, washing with deionized water, and recrystallizing the crude product from dichloromethane to obtain a guanidine-modified benzoxazine;
[0011] (4) Add 1-2 parts by weight of an emulsifier, sodium dodecyl sulfate, and 4-10 parts by weight of vinyl carbon nanotubes to deionized water, and after uniform dispersion, add 6-9 parts by weight of guanidine-modified benzoxazine, 5-10 parts by weight of styrene, and 7-12 parts by weight of boric acid-modified vinyl adamantane, stir evenly, and then dropwise add 0.3-0.5 parts by weight of dibenzoyl peroxide initiator in a nitrogen atmosphere, heat to 70-90° C. for reaction for 3-6 hours, filter the solvent, wash with deionized water and ethanol in turn, and dry to obtain carbon nanotube-modified benzoxazine.
[0012] Preferably, the mass ratio of 5-aminoisophthalic acid to thionyl chloride in (1) is 1:2.2-2.6.
[0013] Preferably, the mass ratio of sulfaguanidine, intermediate 1 and triethylamine catalyst in (2) is 1.1-1.3:1:0.02-0.04.
[0014] Preferably, the mass ratio of the intermediate 2, the aqueous solution of formaldehyde and magnolol in (3) is 1:2.1-2.4:1.8-2.6.
[0015] Preferably, the preparation method of the boric acid modified olefinic adamantane in (4) is as follows: adding boric acid to a toluene solvent, stirring evenly, adding 3-hydroxy-1-adamantyl methacrylate thereto, heating to 90-110° C. to react for 6-10 hours, and then distilling under reduced pressure to obtain the boric acid modified olefinic adamantane.
[0016] Preferably, the mass ratio of the boric acid to 3-hydroxy-1-adamantyl methacrylate is 1:3.1-3.5.
[0017] Preferably, the preparation method of the high temperature resistant flame retardant thermoplastic elastomer is: hydrogenated styrene butadiene block copolymer, paraffin oil, polyethylene wax, and carbon nanotube-modified benzoxazine are extruded and granulated at 175-185° C. in a twin-screw extruder, and then the pellets are compression molded in a flat vulcanizer at a pressure of 10-12 MPa and 175-180° C. to obtain a high temperature resistant flame retardant thermoplastic elastomer.
[0018] (III) Beneficial technical effects
[0019] The invention extrude and granulate hydrogenated styrene butadiene block copolymer, paraffin oil, polyethylene wax and carbon nanotube modified benzoxazine in a twin-screw extruder, and then compression-mold the granules in a flat vulcanizer to obtain a high temperature resistant flame retardant thermoplastic elastomer.
[0020] The nitrogen, sulfur, guanidine, boron and benzoxazine structures in carbon nanotube-modified benzoxazine all have good flame retardant effects. The nitrogen contained in it can produce non-flammable gas when heated, dilute the concentration of flammable gas, and achieve the purpose of flame retardancy; the sulfur element in it produces strong acidic substances when heated, which can promote the dehydration of the substrate into carbon, and play a good flame retardant effect; when the boron element burns, it helps the material to form a porous carbon layer during the combustion process. This carbon layer can stabilize the flame and reduce the release of flammable gases. When heated, the guanidine group will decompose to produce non-flammable gases, such as ammonia and nitrogen. These gases can dilute the oxygen in the air and the flammable gas produced by the thermal decomposition of the polymer, thereby playing a flame retardant role; the benzoxazine structure in it will form a heat-resistant phenolic resin structure at high temperature, making it have a good flame retardant effect. The carbon nanotubes in the carbon nanotube-modified benzoxazine have good high temperature resistance and flame retardant effects, as well as good mechanical properties. The adamantane contained therein also has good mechanical properties. Adding it to the thermoplastic elastomer improves its performance. DETAILED DESCRIPTION
[0021] The preparation process of vinyl carbon nanotubes refers to the journal "Materials Science and Engineering Plastics", Vol. 23, No. 4, "Surface Vinyl Functionalization of Multi-walled Carbon Nanotubes":
[0022] Add 0.3 g of multi-walled carbon nanotubes to 30 mL of 98% concentrated sulfuric acid and 10 mL of 70% concentrated nitric acid, reflux at 140°C for 1 h, filter and wash. Weigh 0.1 g of the acidified carbon nanotubes obtained and disperse them in 15 mL of acetone and 15 mL of chloroform. Add 2 mL of triethylamine and 5 mL of acryloyl chloride, react at 40°C for 24 h, add 10 mL of ethanol and stir for 2 h, filter and wash to obtain vinyl carbon nanotubes.
[0023] Example 1
[0024] (1) Add 5-aminoisophthalic acid and thionyl chloride to a xylene solvent, wherein the mass ratio of 5-aminoisophthalic acid to thionyl chloride is 1:2.2, stir evenly, heat to 75° C., react for 3 h, and then remove the solvent by evaporation under reduced pressure to obtain an intermediate 1;
[0025] (2) adding sulfaguanidine to anhydrous ethanol solvent, stirring evenly, and then adding intermediate 1 and triethylamine catalyst, wherein the mass ratio of sulfaguanidine, intermediate 1, and triethylamine catalyst is 1.1:1:0.02, reacting at 80° C. for 6 hours, cooling to room temperature after completion, filtering, washing, and obtaining intermediate 2;
[0026] (3) adding intermediate 2, an aqueous solution of formaldehyde, and magnolol to a toluene solvent, wherein the mass ratio of intermediate 2, the aqueous solution of formaldehyde, and magnolol is 1:2.1:1.8, fully dissolving, and carrying out a cyclization reaction at 65° C. for 10 h. After completion, distillation under reduced pressure is performed, the product is washed with deionized water, and the crude product is recrystallized from dichloromethane to obtain a guanidine-modified benzoxazine;
[0027] (4) adding boric acid to a toluene solvent, stirring evenly, and then adding 3-hydroxy-1-adamantyl methacrylate, wherein the mass ratio of boric acid to 3-hydroxy-1-adamantyl methacrylate is 1:3.1, heating to 90° C. for 6 h, and then performing reduced pressure distillation to obtain a boronic acid-modified ene-adamantane;
[0028] (5) Add 1 part by weight of emulsifier sodium dodecyl sulfate and 4 parts by weight of vinyl carbon nanotubes to deionized water, and after uniform dispersion, add 6 parts by weight of guanidine-modified benzoxazine, 5 parts by weight of styrene, and 7 parts by weight of boric acid-modified vinyl adamantane, stir evenly, and then drop 0.3 parts by weight of dibenzoyl peroxide initiator in a nitrogen atmosphere, heat to 70° C. for reaction for 3 hours, filter the solvent, wash with deionized water and ethanol in turn, and dry to obtain carbon nanotube-modified benzoxazine;
[0029] (6) 40 parts by weight of hydrogenated styrene butadiene block copolymer, 2 parts by weight of paraffin oil, 1 part by weight of polyethylene wax, and 5 parts by weight of carbon nanotube-modified benzoxazine are extruded and granulated at 175° C. in a twin-screw extruder, and then the granules are compression molded in a flat vulcanizer at a pressure of 10 MPa and at 175° C. to obtain a high temperature resistant flame retardant thermoplastic elastomer.
[0030] Example 2
[0031] (1) Add 5-aminoisophthalic acid and thionyl chloride to a xylene solvent, wherein the mass ratio of 5-aminoisophthalic acid to thionyl chloride is 1:2.6, stir evenly, heat to 90° C., react for 6 h, and then remove the solvent by evaporation under reduced pressure to obtain an intermediate 1;
[0032] (2) adding sulfaguanidine to anhydrous ethanol solvent, stirring evenly, and then adding intermediate 1 and triethylamine catalyst, wherein the mass ratio of sulfaguanidine, intermediate 1, and triethylamine catalyst is 1.3:1:0.04, reacting at 100° C. for 12 hours, and after completion, cooling to room temperature, filtering, and washing to obtain intermediate 2;
[0033] (3) adding intermediate 2, an aqueous solution of formaldehyde, and magnolol to a toluene solvent, wherein the mass ratio of intermediate 2, the aqueous solution of formaldehyde, and magnolol is 1:2.4:2.6, fully dissolving, and carrying out a cyclization reaction at 90° C. for 16 h. After completion, distillation under reduced pressure is carried out, the product is washed with deionized water, and the crude product is recrystallized from dichloromethane to obtain a guanidine-modified benzoxazine;
[0034] (4) adding boric acid to a toluene solvent, stirring evenly, and then adding 3-hydroxy-1-adamantyl methacrylate, wherein the mass ratio of boric acid to 3-hydroxy-1-adamantyl methacrylate is 1:3.5, heating to 110° C. to react for 10 h, and then performing reduced pressure distillation to obtain a boronic acid-modified ene-adamantane;
[0035] (5) Add 2 parts by weight of emulsifier sodium dodecyl sulfate and 10 parts by weight of vinyl carbon nanotubes to deionized water, and after uniform dispersion, add 9 parts by weight of guanidine-modified benzoxazine, 10 parts by weight of styrene, and 12 parts by weight of boric acid-modified vinyl adamantane, stir evenly, and then dropwise add 0.5 parts by weight of dibenzoyl peroxide initiator in a nitrogen atmosphere, heat to 90° C. for reaction for 6 hours, filter the solvent, wash with deionized water and ethanol in turn, and dry to obtain carbon nanotube-modified benzoxazine;
[0036] (6) 60 parts by weight of hydrogenated styrene butadiene block copolymer, 4 parts by weight of paraffin oil, 3 parts by weight of polyethylene wax, and 8 parts by weight of carbon nanotube-modified benzoxazine are extruded and granulated at 185° C. in a twin-screw extruder, and then the granules are compression molded in a flat vulcanizer at a pressure of 12 MPa and at 180° C. to obtain a high temperature resistant flame retardant thermoplastic elastomer.
[0037] Example 3
[0038] (1) Add 5-aminoisophthalic acid and thionyl chloride to a xylene solvent, wherein the mass ratio of 5-aminoisophthalic acid to thionyl chloride is 1:2.4, stir evenly, heat to 85° C., react for 5 h, and then remove the solvent by evaporation under reduced pressure to obtain an intermediate 1;
[0039] (2) adding sulfaguanidine to anhydrous ethanol solvent, stirring evenly, and then adding intermediate 1 and triethylamine catalyst, wherein the mass ratio of sulfaguanidine, intermediate 1, and triethylamine catalyst is 1.2:1:0.03, reacting at 90° C. for 9 hours, cooling to room temperature after completion, filtering, washing, and obtaining intermediate 2;
[0040] (3) adding intermediate 2, an aqueous solution of formaldehyde, and magnolol to a toluene solvent, wherein the mass ratio of intermediate 2, the aqueous solution of formaldehyde, and magnolol is 1:2.3:2.4, fully dissolving, and carrying out a cyclization reaction at 80° C. for 13 h. After completion, distillation under reduced pressure is carried out, the product is washed with deionized water, and the crude product is recrystallized from dichloromethane to obtain a guanidine-modified benzoxazine;
[0041] (4) adding boric acid to a toluene solvent, stirring evenly, and then adding 3-hydroxy-1-adamantyl methacrylate, wherein the mass ratio of boric acid to 3-hydroxy-1-adamantyl methacrylate is 1:3.2, heating to 100° C. to react for 8 hours, and then distilling under reduced pressure to obtain a boronic acid-modified ene-adamantane;
[0042] (5) Add 1 part by weight of emulsifier sodium dodecyl sulfate and 7 parts by weight of vinyl carbon nanotubes to deionized water, and after uniform dispersion, add 8 parts by weight of guanidine-modified benzoxazine, 7 parts by weight of styrene, and 11 parts by weight of boric acid-modified vinyl adamantane, stir evenly, and then drop 0.4 parts by weight of dibenzoyl peroxide initiator in a nitrogen atmosphere, heat to 80° C. for 4 hours, filter the solvent, wash with deionized water and ethanol in turn, and dry to obtain carbon nanotube-modified benzoxazine;
[0043] (6) 50 parts by weight of hydrogenated styrene butadiene block copolymer, 3 parts by weight of paraffin oil, 2 parts by weight of polyethylene wax, and 6 parts by weight of carbon nanotube-modified benzoxazine are extruded and granulated at 180° C. in a twin-screw extruder, and then the granules are compression molded in a flat vulcanizer at a pressure of 11 MPa and 178° C. to obtain a high temperature resistant flame retardant thermoplastic elastomer.
[0044] Example 4
[0045] (1) Add 5-aminoisophthalic acid and thionyl chloride to a xylene solvent, wherein the mass ratio of 5-aminoisophthalic acid to thionyl chloride is 1:2.2, stir evenly, heat to 75° C., react for 3 h, and then remove the solvent by evaporation under reduced pressure to obtain an intermediate 1;
[0046] (2) adding sulfaguanidine to anhydrous ethanol solvent, stirring evenly, and then adding intermediate 1 and triethylamine catalyst, wherein the mass ratio of sulfaguanidine, intermediate 1, and triethylamine catalyst is 1.1:1:0.02, reacting at 80° C. for 6 hours, cooling to room temperature after completion, filtering, washing, and obtaining intermediate 2;
[0047] (3) adding intermediate 2, an aqueous solution of formaldehyde, and magnolol to a toluene solvent, wherein the mass ratio of intermediate 2, the aqueous solution of formaldehyde, and magnolol is 1:2.4:2.6, fully dissolving, and carrying out a cyclization reaction at 90° C. for 16 h. After completion, distillation under reduced pressure is carried out, the product is washed with deionized water, and the crude product is recrystallized from dichloromethane to obtain a guanidine-modified benzoxazine;
[0048] (4) adding boric acid to a toluene solvent, stirring evenly, and then adding 3-hydroxy-1-adamantyl methacrylate, wherein the mass ratio of boric acid to 3-hydroxy-1-adamantyl methacrylate is 1:3.5, heating to 110° C. to react for 10 h, and then performing reduced pressure distillation to obtain a boronic acid-modified ene-adamantane;
[0049] (5) Add 1 part by weight of emulsifier sodium dodecyl sulfate and 7 parts by weight of vinyl carbon nanotubes to deionized water, and after uniform dispersion, add 8 parts by weight of guanidine-modified benzoxazine, 7 parts by weight of styrene, and 11 parts by weight of boric acid-modified vinyl adamantane, stir evenly, and then drop 0.4 parts by weight of dibenzoyl peroxide initiator in a nitrogen atmosphere, heat to 80° C. for 4 hours, filter the solvent, wash with deionized water and ethanol in turn, and dry to obtain carbon nanotube-modified benzoxazine;
[0050] (6) 50 parts by weight of hydrogenated styrene butadiene block copolymer, 3 parts by weight of paraffin oil, 2 parts by weight of polyethylene wax, and 6 parts by weight of carbon nanotube-modified benzoxazine are extruded and granulated at 180° C. in a twin-screw extruder, and then the granules are compression molded in a flat vulcanizer at a pressure of 11 MPa and 178° C. to obtain a high temperature resistant flame retardant thermoplastic elastomer.
[0051] Comparative Example 1
[0052] The difference between this comparative example and Example 4 is that no carbon nanotubes are added to modify the benzoxazine.
[0053] The oxygen index of thermoplastic elastomer is tested by oxygen index tester, and the combustion grade of thermoplastic elastomer is tested by horizontal and vertical combustion tester.
[0054] Table 1: Flame retardancy tests.
[0055]
[0056]
[0057] It can be seen from Table 1 that Examples 1-4 of the present invention have better flame retardant effects than Comparative Example 1.
[0058] The thermal properties of thermoplastic elastomers were tested by thermogravimetric analyzer in nitrogen atmosphere, with a heating rate of 25 °C / min and a maximum temperature of 800 °C.
[0059] Table 2: High temperature resistance test.
[0060] project Temperature at which mass loss is 20% (℃) Temperature at which mass loss is 50% (℃) Example 1 463.2 504.2 Example 2 468.6 508.7 Example 3 464.6 503.5 Example 4 467.5 506.8 Comparative Example 1 440.3 482.3
[0061] As can be seen from Table 2, for the thermoplastic elastomers prepared in the present invention, the temperatures at which the mass loss is 20% and 50% in Examples 1-4 are higher than that in Comparative Example 1, indicating that they have better high temperature resistance.
[0062] The tensile properties were tested by a tensile testing machine with a tensile rate of 10 mm / min and a sample size of 70 mm × 6 mm.
[0063] Table 3: Tensile tests.
[0064] project Tensile strength(Mpa) Elongation at break (%) Example 1 41.6 141.5 Example 2 44.7 146.9 Example 3 43.5 143.8 Example 4 42.6 142.9 Comparative Example 1 27.3 110.5
[0065] As shown in Table 3, Examples 1-4 of the present invention have better tensile strength and elongation at break than Comparative Example 1;
[0066] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A high temperature resistant flame retardant thermoplastic elastomer, characterized in that: The invention comprises the following components by weight: 40-60 parts by weight of hydrogenated styrene butadiene block copolymer, 2-4 parts by weight of paraffin oil, 1-3 parts by weight of polyethylene wax, and 5-8 parts by weight of carbon nanotube-modified benzoxazine.
2. The high temperature resistant flame retardant thermoplastic elastomer according to claim 1, characterized in that: The preparation method of the carbon nanotube-modified benzoxazine is as follows: (1) Add 5-aminoisophthalic acid and thionyl chloride to xylene solvent, stir evenly, heat to 75-90° C., react for 3-6 hours, and then remove the solvent by evaporation under reduced pressure to obtain intermediate 1; (2) adding sulfaguanidine to anhydrous ethanol solvent, stirring evenly, then adding intermediate 1 and triethylamine catalyst, reacting at 80-100° C. for 6-12 hours, and after completion, cooling to room temperature, filtering, washing, and obtaining intermediate 2; (3) adding intermediate 2, an aqueous solution of formaldehyde, and magnolol to a toluene solvent, fully dissolving them, and carrying out a cyclization reaction at 65-90° C. for 10-16 hours. After completion, the reaction is carried out by vacuum distillation, washing with deionized water, and recrystallizing the crude product from dichloromethane to obtain a guanidine-modified benzoxazine; (4) Add 1-2 parts by weight of an emulsifier, sodium dodecyl sulfate, and 4-10 parts by weight of vinyl carbon nanotubes to deionized water, and after uniform dispersion, add 6-9 parts by weight of guanidine-modified benzoxazine, 5-10 parts by weight of styrene, and 7-12 parts by weight of boric acid-modified vinyl adamantane, stir evenly, and then dropwise add 0.3-0.5 parts by weight of dibenzoyl peroxide initiator in a nitrogen atmosphere, heat to 70-90° C. for reaction for 3-6 hours, filter the solvent, wash with deionized water and ethanol in turn, and dry to obtain carbon nanotube-modified benzoxazine.
3. The high temperature resistant flame retardant thermoplastic elastomer according to claim 2, characterized in that: The mass ratio of 5-aminoisophthalic acid to thionyl chloride in (1) is 1:2.2-2.
6.
4. The high temperature resistant flame retardant thermoplastic elastomer according to claim 2, characterized in that: The mass ratio of sulfaguanidine, intermediate 1 and triethylamine catalyst in (2) is 1.1-1.3:1:0.02-0.
04.
5. The high temperature resistant flame retardant thermoplastic elastomer according to claim 2, characterized in that: The mass ratio of the intermediate 2, the aqueous solution of formaldehyde and magnolol in (3) is 1:2.1-2.4:1.8-2.
6.
6. The high temperature resistant flame retardant thermoplastic elastomer according to claim 2, characterized in that: The preparation method of the boric acid modified olefin adamantane in (4) is as follows: adding boric acid to a toluene solvent, stirring evenly, adding 3-hydroxy-1-adamantyl methacrylate thereto, heating to 90-110° C. for reaction for 6-10 hours, and then performing reduced pressure distillation to obtain the boric acid modified olefin adamantane.
7. The high temperature resistant flame retardant thermoplastic elastomer according to claim 6, characterized in that: The mass ratio of the boric acid to 3-hydroxy-1-adamantyl methacrylate is 1:3.1-3.
5.
8. A method for preparing a high temperature resistant flame retardant thermoplastic elastomer according to any one of claims 1 to 7, characterized in that: The preparation method of the high temperature resistant flame retardant thermoplastic elastomer comprises: extruding hydrogenated styrene butadiene block copolymer, paraffin oil, polyethylene wax and carbon nanotube modified benzoxazine in a twin-screw extruder at 175-185° C. to form granules, and then molding the granules in a flat vulcanizer at 175-180° C. under a pressure of 10-12 MPa to obtain the high temperature resistant flame retardant thermoplastic elastomer.
Citation Information
Patent Citations
High-temperature-resistant thermoplastic elastomer and preparation method thereof
CN106674843A
Cited By
High-strength CPVC pipe and preparation method thereof
CN121851581A